Analysis of air pollution reduction and climate change mitigation in the industry sector of Yangtze River Delta in China - Zheng, Jiajia; Jiang, Ping; Qiao, Wen; Zhu, Yun; Kennedy, Erin ; 0000-0002-5262-3897 (Journal of Cleaner Production, 2016)
China is now undergoing a fast process of industrialization, with the industry sector playing an important role in the overall economy. Among the many economic areas in China, Yangtze River Delta (YRD) takes the lead. The macro economy development and energy use status quo of both China and YRD are depicted, the past and current situation of air pollution and GHGs emissions is presented, and detailed national and local policies are reviewed. GAINS-China model is deployed in this study to evaluate the air pollution reduction and climate change mitigation achievements in the industry sector under the current policy of the three areas (i.e. Jiangsu, Zhejiang and Shanghai) in YRD from 2005 to 2030. According to the simulation results, the total population would grow marginally while the economy of YRD will keep booming in the next two decades. The total energy consumption of Jiangsu, Zhejiang and Shanghai in 2030 would be 2.36, 2.61 and 1.81 times that of 2005, with the industry sector still playing the biggest part. SO2 emissions would be well under-control by 2030. The NOX emissions all show steady growing trends, while the PM2.5 emissions show different trends for three areas. The ensemble average years of life lost has a complex correlation with the total population and the PM2.5 concentration. CO2 emissions are still in predominant position among all the GHGs emissions, showing a steady growing trend towards 2030. All GHGs emissions amount in YRD would be 1.76 times that of 2005. The differences among the emissions in the three areas may due to reasons like economy scale, industrial composition, energy structure, and enforcement rate of policy. The uncertainties of this study may come from inaccurate prediction of scenario parameters and the expected policy changes in the future, and the emissions from the restructure of industry should be considered as well. In terms of achieving sustainable industrial development, YRD's governments should restrict the scale of energy-intensive industries, improve the primary energy structure, and take co-benefits concepts and methods more into policy-making processes.
Publisher Copyright: © 2015 Elsevier Ltd.
Keywords: Air pollution; Co-benefits; GAINS-model; GHGs; Industry sector; Yangtze River Delta